PENGEMBANGAN BUKU ILMIAH POPULER KEANEKARAGAMAN ZINGIBERACEAE DI DESA BARIMBUN KABUPATEN TABALONG SEBAGAI BAHAN PENGAYAAN MATA KULIAH PHANEROGAMAE - Khoirunnisa Khoirunnisa; Bunda Halang; Riya Irianti (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The development of popular scientific books with local potential is believed to be able to support learning resources based on local potential. Popular scientific books are structured as learning resources for enrichment materials for the Zingiberidae subclass in the Phanerogamae course. Known as the ginger family, Zingiberaceae is widely used in Southeast Asia, especially Indonesia for its unique taste, ornamental appeal, and medicinal value. The purpose of this study was to describe the species diversity of Zingiberaceae in Barimbun Village, Tabalong Regency, and to describe the suitability, feasibility, and readability of the results of the development of a popular scientific book on Zingiberaceae Diversity in Barimbun Village, Tabalong Regency. The research method used is research and development (R&D) concerning the 4D development model. Â Based on the research results, 7 species were obtained consisting of the genera Amomum, Alpinia, Curcuma, Zingiber, and Kaempferia. The results of the suitability test were stated to be very suitable with a value of 4.5. The results of the feasibility test were declared very feasible with a value of 4.3. The results of the readability test by students were stated to be very good with a value of 4.5.Â Â